Biotechnology as an Advanced Science - Hanaa Daaj Khalaf Al-Mozan, Nassir Abdullah Hillo, Hussam Saadi Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Using of biotechnology has increased in recent times, in turn, the excessive use of molecular biology, biochemistry, cell biology, embryology, genetics, and microbiology to carry out this technique has also increased, as the sciences on which biotechnology is based. There is no doubt that the application of these sciences must leave fears or negative effects on living organisms and the environment. It should be noted that when the use of modern technologies increased, the emergence of incurable diseases such as cancer and congenital malformations has increased, which calls for caution in using this technology and not using it except in cases of extreme necessity. Keywords: Biotechnology, Gene therapy, Genetically modified food, Medicine